Pharmacologic Properties of the Carrier Solutions for Hyperthermic Intraperitoneal Chemotherapy: Comparative Analyses Between Water and Lipid Carrier Solutions in the Rat Model - Park, Eun Jung; Ahn, Junhyun; Gwak, Sang Won; Park, Kyung Su; Baik, Seung Hyuk; Hwang, Sung-Joo (SPRINGER, 2018)
Carrier solutions play an important role in the distribution, plasma absorption, chemical stability, and solubility of anticancer agents during hyperthermic intraperitoneal chemotherapy (HIPEC). In the current study, lipophilic properties of carrier solutions were evaluated to determine whether they improved anticancer drug absorption rates using mitomycin-C (MMC) or oxaliplatin HIPEC as compared to hydrophilic carrier solutions. Sprague-Dawley rats were divided into two groups: MMC and oxaliplatin treatment groups. Each group was then further subdivided by carrier solution: Dianeal(A (R)) PD-2 peritoneal dialysis solution, 5% dextrose solution and 20% lipid solution (Lipision(A (R))). HIPEC was performed over 60 min at 41-42 A degrees C using the anticancer drugs MMC (35 mg/m(2)) or oxaliplatin (460 mg/m(2)). The plasma area under the curve (AUC; AUC(plasma)), peritoneal AUC (AUC(peritoneum)), and peritoneal/plasma AUC ratios were compared among HIPEC carrier solutions. Plasma drug concentrations were significantly different among carrier solutions, varying by time. In contrast, peritoneal drug concentrations did not change with carrier solution. In the MMC group, the peritoneal/plasma AUC ratio of a lipid solution was three times higher than Dianeal(A (R)) (p < 0.001). In the oxaliplatin group, the peritoneal/plasma AUC ratio was significantly different between carrier solutions (p = 0.046). Although the oxaliplatin AUC(peritoneum) did not vary (p = 0.941), the AUC(plasma) of a lipid solution was lower than that of 5% dextrose solution (p = 0.039). The lipid carrier solution increases the peritoneal/plasma AUC ratio and decreases plasma absorption rates. However, further study is required before clinical uses, considering its pharmacologic properties and possible risks after HIPEC.
Keywords: PERITONEAL CARCINOMATOSIS; TISSUE DISTRIBUTION; COMPLETE RESECTION; OXALIPLATIN; PHARMACOKINETICS; CANCER; MALIGNANCY; IRINOTECAN; SURGERY; THERAPY